Embolic protection in patients undergoing transaortic transcatheter aortic valve replacement: initial experience with the TriGuard HDH embolic deflection device. Issue 10 (30th August 2016) - Campelo‐Parada, Francisco; Regueiro, Ander; Dumont, Eric; DeLarochellière, Robert; Paradis, Jean‐Michel; Mohammadi, Siamak; Doyle, Daniel; Rodés‐Cabau, Josep
Abstract: BACKGROUND: Stroke remains one of the most worrisome complications following transcatheter aortic valve replacement (TAVR). This pilot study evaluates the safety, feasibility, and exploratory efficacy of the TriGuard HDH embolic deflection device (Keystone Heart Ltd., Caesarea, Israel) in patients undergoing transaortic TAVR. METHODS: A total of 10 patients (median age: 81 years, STS score: 9.6 ± 5.6%) undergoing transaortic TAVR were included. All 30‐day events were recorded and defined according to Valve Academic Research Consortium‐2 criteria. Cerebral diffusion‐weighted magnetic resonance imaging exams were planned preprocedure and within 10 days post‐TAVR. The results of the magnetic resonances were analyzed in an independent core laboratory blinded to clinical data. Neurocognitive evaluation tests (Montreal Cognitive Assessment, Cogstate, Digit Symbol Substitution Test, Word Fluency Test, and Trailmaking tests) were performed at baseline, and within 10 and 30 days post‐TAVR. RESULTS: The TriGuard HDH device was successfully deployed in all patients without complications. There was one procedural major vascular complication unrelated to the study device, and no clinically apparent stroke events were observed at 30‐day follow‐up. Cerebral diffusion weighted magnetic resonance imaging exams were performed in six patients at 7.5 ± 1.9 days post‐TAVR showing the presence of new ischemic lesions in five patients (83.3%), which were single lesions in 60% of these individuals. Paired neurocognitive evaluation tests demonstrated no significant changes in neurocognitive parameters over time. CONCLUSIONS: This study shows the safety and feasibility of using the TriGuard HDH embolic protection device in transaortic TAVR. Further studies are warranted to determine the efficacy of embolic protection in this population.